Effect of dietary phytase supplementation on greenhouse gas emissions from soil after swine manure application. (10th November 2017) - Yitbarek, Alexander; López, Secundino; Tenuta, Mario; Asgedom, Haben; France, James; Nyachoti, Charles Martin; Kebreab, Ermias
Abstract: Effects of supplementing swine diets with phytase on manure composition and greenhouse gas (GHG) emissions from soil after manure application were investigated. The experiment was laid out in a completely randomised 3 × 2 × 2 factorial design, with three manure treatments (no manure, manure from unsupplemented diet and manure from phytase supplemented), two soils (Carman and Gunton sandy loam soils from Southern Manitoba, Canada) and two moisture levels (low and high moisture with 0.50 and 0.80 water-filled pore space, respectively). Gas emissions were greater ( P  < 0.05) from high than from low moisture soils. Manure addition increased CO2 and N2 O emissions. When applied to high moisture soils, CO2 emission was increased and that of N2 O decreased when phytase manure was applied compared with non-phytase manure. Methane emission was not affected by manure addition or by type of manure applied. Inorganic N remaining in soil at the end of the experiment was greater with phytase than with non-phytase manure application. Plant extractable P concentrations in soil were reduced with phytase manure, probably due to lower total P added with the manure. For a successful dietary strategy to reduce GHG from manure, a good understanding of the soil properties that influence emissions becomes necessary. Supplementation of swine diets with phytase contributes to reduce disposal of P and N in manure, but has a limited effect on GHG emissions from manure amended soils. Emission of N2 O may be reduced using manure from piglets fed phytase supplemented diets to fertilise high moisture soils. Highlights: Manure from pigs fed phytase diets decreases disposal of P and N to land. CO2 and N2 O released after manure application depend on soil type and moisture. CO2 and CH4 from pig-manure amended soils are not affected by feeding phytase diets. N2 O from high moisture soils are lower using manure from pigs fed phytase diets.